1981
DOI: 10.7326/0003-4819-95-1-28
|View full text |Cite
|
Sign up to set email alerts
|

Menopausal Estrogen Therapy and Hip Fractures

Abstract: The association between menopausal estrogen therapy and hip fracture was studied in a retirement community. Ninety-one hip fracture cases during a 5-year period in female residents under age 80 were compared to age-and race-matched community controls. Estrogen use was recorded from the medical records of the outpatient care facility and personal interviews. The estimated risk ratio for use of oral estrogens in excess of 60 months was 0.42. This protective effect was largely limited to oophorectomized women for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
60
0
2

Year Published

1983
1983
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 447 publications
(72 citation statements)
references
References 12 publications
9
60
0
2
Order By: Relevance
“…The relative risk for hip fracture was almost twice as high among women who performed outdoor loadbearing activities less than once a day compared with subjects who performed these activities every day (Table 3). These findings concur with the results of crosssectional studies conducted in Caucasian populations living in the United Kingdom [16] and United States [17]. Moreover, a 14-year prospective study in the United Kingdom has confirmed the relationship between lack of activity and hip fracture [18].…”
Section: Lifestyle Factorssupporting
confidence: 82%
“…The relative risk for hip fracture was almost twice as high among women who performed outdoor loadbearing activities less than once a day compared with subjects who performed these activities every day (Table 3). These findings concur with the results of crosssectional studies conducted in Caucasian populations living in the United Kingdom [16] and United States [17]. Moreover, a 14-year prospective study in the United Kingdom has confirmed the relationship between lack of activity and hip fracture [18].…”
Section: Lifestyle Factorssupporting
confidence: 82%
“…In several case-control studies, customary physical inactivity was found to be an independent risk factor for hip fracture in elderly people [10,12,36,60,73]. In accordance with these cross-sectional reports, recent prospective data have confirmed that decreased levels of physical activity are associated with a substantially increased risk of hip fracture [18,72,90].…”
Section: Physical Inactivitysupporting
confidence: 67%
“…In line with these densitometric data, current smoking was found to be associated with an increased risk of hip fracture, both in case-control and most (but not all) prospective population-based studies [18,32,41,60,61,72,73,90,91]. The exact mechanism underlying this association has not been established but may be mediated through an effect of smoking on estrogen metabolism and calcium absorption [46,54].…”
Section: Caffeine Intake Smoking and Alcohol Consumptionsupporting
confidence: 49%
See 1 more Smart Citation
“…Through an antiresorptive mechanism, estrogen therapy has been shown to be effective in preserving cortical and trabecular bone in both the peripheral and axial skeleton at all stages of postmenopausal life [6]. Epidemiologic studies have consistently reported that estrogen therapy reduces the risk of vertebral, hip and forearm fractures in postmenopausal women [7][8][9][10][11][12][13], while only limited data are available from randomized clinical trials [14].…”
Section: Introductionmentioning
confidence: 99%